On Gaps in the Orders of Complete Groups of Isometry and Homoteties in Specialized Riemannian Spaces and Metrics of the Most Mobile of These Spaces of the First Six Lacunars - Z. N. Chetyrkina (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
In the present paper there are considered metric Riemannian spaces  Vn4a,  in the metrics of which four algebraic structures work at once: real numbers  Dm1 and  complex numbers  Cm2, quaternions  Hm3 and octions  Om4. We are interested in these spaces in terms of their isometric and homothetic mobility. It turns out that there are lacunas (gaps) in the orders  r of complete groups of isometries  Gr and homotheties Pr. The metrics of the most mobile spaces  Vn4a of the first six lacunarities in the sense of I. P. Egorov are found.